Study of mechanical properties of commercial biopolymers concerning the effect of microbial decomposition in compost I - Puková, Kateřina; Janda, Tomáš; Večeřa, Miroslav; Rückerová, Adéla (University of Pardubice, 2018)
This paper focuses on the verification of properties declared by the manufacturer and, above all, on the confirmation of biodegradability of commercially available polymer blends of the Envira© series produced by TART. This company provided two types of compostable polymer blends based on polylactic acid and starch (further specifications were not available). For this reason, the concerned samples were subjected to infrared spectroscopy and gas chromatography with a mass spectrometer to determine the secondary components contained in the material. The main objective of this work was to map the behaviour and properties of polymer mixtures in an environment rich in microorganisms, i.e. compost. The extent of degradation was evaluated by comparing the results of the mechanical attributes of the samples tested, as well as their structural changes visible in a scanning electron microscope.
Keywords: biopolymers; mechanical properties; degradation; compost